Перспективы освоения газоугольных месторождений Западного Донбасса - Булат, А.Ф.; Пимоненко, Л.И.; Безручко, К.А.; Приходченко, А.В.; Пимоненко, Д.Н. (Геотехническая механика, 2012)
Проаналізовані геологічні умови газоносності середнього карбону Західного Донбасу. В межах Лозовського району виділені найбільш перспективні інтервали і оцінена потенційна газонасиченість пісковиків. На підставі отриманих даних зроблено висновок про необхідність постановки геологічних робіт для вивчення можливості комплексної утилізації газів: з верхніх горизонтів (до 1000 м) азоту і з нижніх (1000 – 1800м і більш) – метану. The geological conditions of gas-bearing middle carbon Western Donbass are analysed. In limits area Lozovsk district the most perspective intervals are selected and the potential gas-saturation of sandstones is appraised. On the basis of the received data a conclusion is done about the necessity statement of geological works for studying an possibility of complex utilization gases: from upper horizons (to 1000 meter) of nitrogen and from lower (1000 – 1800 meter and more) – methane.